Simulation on linearity of fabry-perot semiconductor laser for radio over fibre system - Quak,, Sek Jade @ Grace (Universiti Malaysia Sarawak, UNIMAS, 2001)
The main concern in this research is on the linear operating section in laser diode at remote unit of radio over the fibre system. The purposes of this laser serve as a device to convert electrical signal into optical signal to link into optical fibre cable. Direct intensity modulation is important to operate in the linear region of a laser. Fabry-Perot laser has been proven to be applicable in CATV (Cable Television) thus transmission of audio signal in mobile would not be doubtful. Escalate demand on bandwidth, add value and less distortion in mobile communication subscriber urges operator to make improvement thus, radio over fibre presently is the solution to this problem.